The right to live and die / Abdul Halim Mohamed Dalib - Mohamed Dalib, Abdul Halim (Faculty of Law, 1983)
'The Right to Live and Die t is a topic which is very controversial and sensitive ill nature, as the core of the discussion centres around the question of life and death, particularly the rights of an individual over his own life and death. The areas within the framework of this topic is extensive, and the writer therefore decided to limit the discussion to three important issues, that is, pertaining to Suicide, Euthanasia and Abortion, as discussed in Chapter 1, 2 and 3 respectively.